2018
DOI: 10.1097/hnp.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Care on Adolescents Coping With Cancer

Abstract: People's experiences of living with cancer suggest that spirituality creates purpose and meaning in life for patients. Strengthening spirituality has positive effects on coping, mental health, and symptoms of the disease. This study examines the effect of spiritual care on adolescents coping with cancer. This research is a single-group, quasi-experimental, pre-/poststudy conducted on 32 adolescents. The spiritual care program was presented individually and face to face over six 45-minute sessions held on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…The results of this study showed that the scores of existential spiritual health, religious-spiritual health score and overall spiritual health of adolescents increased after the intervention and showed a positive effect of the intervention on spiritual health. In this regard, the results of some studies show the positive effects of spiritual care on adaptation (24), anxiety (32) and self-confidence (33), which are in line with the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study showed that the scores of existential spiritual health, religious-spiritual health score and overall spiritual health of adolescents increased after the intervention and showed a positive effect of the intervention on spiritual health. In this regard, the results of some studies show the positive effects of spiritual care on adaptation (24), anxiety (32) and self-confidence (33), which are in line with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Given the lack of title-related study and considering the role of religious beliefs and spirituality in coping with crises and illnesses, the mean and standard deviation score taken by Torabi et al (24) study were considered the closest and the most relevant study for the sample size used. The mean and standard deviation (SD) was the direct adaptation index score in Torabi et al (24) study as 5.59 ± 122.7.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in this study believed that following medical guidelines and protocols and recognizing and controlling errors and risks could enhance patient safety culture. In this regard, the study by Torabi et al (2018) also emphasizes this claim and believes that the culture of principled reporting of errors versus concealment of errors; punitive culture and inspection versus incentive culture in dealing with errors; evaluating errors with an individual approach to a systemic approach; organizational learning and sharing experiences of errors; establishing an organizational mission based on compliance with patient safety standards and preventive corrective actions, errors, teamwork culture, and compliance with patient legal rights can improve patient safety (28). The results of the study by khoshoei and Salehi (2018) also showed that o cials' views on the process of reporting work errors (the need to report, barriers to reporting and facilitating reporting factors), the response of o cials to work errors (why to deal with error, type of reaction, the need to t the type of error encounter), and solutions to reduce errors (holding training classes, reducing workload (nurse-patient ratio), reducing multiple shifts, reviewing the educational process of nursing students) are some of the ways to increase patient safety (29).…”
Section: Discussionmentioning
confidence: 97%